Cu–iminopyridine complexes as catalysts for carbene and nitrene transfer reactions. (21st May 2014) - Abedi, Yaghoub; Biffis, Andrea; Gava, Riccardo; Tubaro, Cristina; Chelucci, Giorgio; Stoccoro, Sergio
<x xml:space="preserve">Abstract</x> Copper complexes with chiral iminopyridine ligands were screened for their catalytic efficiency in carbene (cyclopropanation) and nitrene transfer reactions (aziridination, CH amidation). Both pre‐formed and in situ formed complexes were considered. The results highlighted the poor catalytic efficiency of these complexes in cyclopropanation reactions employing methyl phenyldiazoacetate as the carbene source, whereas better results were obtained in nitrene transfer reactions, particularly in the amidation of CH bonds, albeit the enantioselectivity of the reactions was negligible in nearly all cases. Finally, copper complexes were also found to promote an interesting oxidative functionalization of alkynes with PhI(OAc)2 at room temperature. Copyright © 2014 John Wiley & Sons, Ltd.